Wykorzystanie mezzanine capital do pokonywania luki kapitałowej - Węcławski, Jerzy (Mezzanine Capital as a Bridge to Close o Capital Gap, 2006)
Mezzanine capital is of importance for unlisted small and medium sized enterprises which Haunter difficulties in raising own and foreign capital. Mezzanine capital falls in between the two types of capital. The vast scope of mezzanine capital instruments ensures meeting various situational needs of enterprises. Mezzanine capital instruments include: mezzanine debt, preference shares, equity mezzanine capital with warrant, equity mezzanine capital with shadow warrant, equity mezzanine capital with convertible right. Mezzanine capital is predominantly used in financing expansion, mergers and acquisitions, going public, financial restructuring, and ownership transformations. The major advantage on the part of an entrepreneur is that his position in a company mains unaffected. Mezzanine capital investors safeguard their rights by way of legal covenants and financial covenants.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1109, s. 683-693